Heterogeneity of Powdery Mildew Resistance Revealed in Accessions of the ICARDA Wild Barley Collection - Dreiseitl, Antonin (Frontiers in Plant Science, 2017)
The primary gene pool of barley comprises two subspecies - wild barley (Hordeum vulgare subsp. spontaneum) and cultivated barley H.v. subsp. vulgare. The former originated 5.5 million years ago in southwest Asia and is the immediate ancestor of cultivated barley, which arose around 10,000 years ago. In this study, the specific resistance of a set of 146 wild barley accessions, maintained by the International Center for Agriculture Research in the Dry Areas (ICARDA), to 32 isolates of barley powdery mildew caused by Blumeria graminis f. sp. hordei was evaluated. The set comprised 146 heterogeneous accessions of a previously tested collection. Seed was obtained by single seed descent and each accession was usually represented by five single plant progenies. In total, 687 plant progenies were tested. There were 211 phenotypes of resistance among the accessions, 87 of which were found in single plants, while 202 plants contained the eight most common phenotypes. The most frequent phenotype was found in 56 plants that were susceptible to all pathogen isolates, whereas the second most frequent phenotype, which occurred in 46 plants, was resistant to all isolates. The broad resistance diversity that was revealed is of practical importance and is an aid to determining the extent and role of resistance in natural ecosystems.